ROTARY SOOT BLOWING TREATMENT INCREASES EFFECTIVENESS OF ECONOMIZER CAPACITY OF 58.5 TPH AT PT SBI INDONESIA - Harianto, Agus; Aspiyansyah, Aspiyansyah; Rahman, Muhammad Muksin Galih (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2024)
In an industrial era that increasingly prioritizes energy efficiency and environmental sustainability, optimizing the use of energy in the production process is crucial. One of the key aspects of achieving this goal is utilizing waste heat to improve the overall efficiency of the system. In this context, the use of economizers has become a major focus in the boiler industry. PT Surya Borneo Industri (SBI), as an industrial entity committed to energy efficiency and environmental sustainability, has adopted the latest technology in a bid to improve the performance of their boiler system. One of the latest innovations they have implemented is the use of rotary soot blowing, an automated device designed to clean the heat exchanger surfaces in the economizer. This study aims to determine the effectiveness value of the economizer before and after the rotary soot blowing treatment on the PT SBI boiler system. Through a series of field observations and data analysis, this research reveals the potential benefits of using rotary soot blowing in improving thermal efficiency, reducing energy losses, and contributing to the sustainability of industrial operations. The results obtained showed that the economizer effectiveness value before the rotary soot blowing treatment was 55, 54, 55, and 54%, and after the rotary soot blowing treatment, the effectiveness value increased to 59, 60, 61, and 60%. This is due to maintenance activities, namely cleaning dust or soot attached to the economizer pipes.